Sevoflurane Exposure in the Developing Brain Induces Hyperactivity, Anxiety–Free, and Enhancement of Memory Consolidation in Mice - Li, Rui; Wang, Bei; Cao, Xiaohong; Li, Chao; Hu, Yuhan; Yan, Dandan; Yang, Yanchang; Wang, Liqing; Meng, Lingzhong; Hu, Zhiyong (Frontiers in Aging Neuroscience, 2022)
Background Sevoflurane exposure at brain developmental stages has been reported to induce neurotoxicity and subsequently results in learning deficits at the juvenile age. In this study, we aim to investigate the effects of prior early-age sevoflurane exposure on locomotor activity, anxiety, CA1-dependent learning, and spatial memory as well as synapse changes in mice. Methods 3% sevoflurane was given to neonatal mice at postnatal day 7 for 4 hours. These sevoflurane-treated mice were later subjected to open field and Morris Water maze tests at their adult age (postnatal day 60-90) to assess their motor activity and spatial learning ability, respectively. The brain slices of sevoflurane-treated and control mice were examined for dendritic spine density and Long-Term Potentiation (LTP) features following behavior tests (postnatal day 60). Protein levels of NMDA receptor subtypes and PSD95 in brain lysate were measured by using immunoblotting at the same age (postnatal day 60). Results Prior early-age sevoflurane exposure increased the overall moving distance, prolonged the central-area lingering time, and increased the central-area entries of adult mice. Sevoflurane-treated mice spent more time in the target quadrant during the Probe test. An increase of the spine density of pyramidal neurons in the CA1 region was observed in Sevoflurane-treated mice. NMDA receptor GluN2A subunit, but not the GluN2B or PSD95, was increased in the brain lysate of Sevoflurane-treated mice compared to that of control mice. LTP in the hippocampus did not significantly differ for Sevoflurane-treated and control mice. Conclusion Exposure to sevoflurane for mice during an early brain developmental stage (P7) induces later-on hyperactivity，anxiety free and enhancement of memory retention. These observations shed light on future investigations on the underlying mechanisms of sevoflurane’s effect on neuronal development.